HEALTH IMPLICATIONS OF OBESITY AND HYPERTENSION IN NIGERIAN SCHOOL-AGED ADOLESCENTS - Adebayo , Olumide Adeyemi; Smith, Michael Andrew (American Research Journal of Nursing and Health Sciences (ARJNHS), 2024)
Overweight and obesity have emerged as significant global health concerns, with their prevalence escalating to epidemic proportions. In many developing countries, these conditions are mistakenly perceived as indicators of affluence and well-being, despite their substantial health risks (Qorbani et al., 2013). Obesity, characterized by excessive fat accumulation, is a complex condition resulting from an interplay of environmental factors, genetic predisposition, and behavioral patterns. It is strongly linked to an increased risk of several chronic diseases, including cardiovascular disorders, diabetes, and other systemic conditions (Yang and Kelly, 2007). This growing health crisis contributes to a heightened burden of cardiovascular diseases, strokes, and premature mortality worldwide (Qorbani et al., 2013). Addressing the multifaceted nature of obesity requires comprehensive strategies that integrate public health initiatives, behavioral changes, and environmental modifications to mitigate its impact and improve overall health outcomes